2020
DOI: 10.1038/s41396-020-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

Dual energy metabolism of the Campylobacterota endosymbiont in the chemosynthetic snail Alviniconcha marisindica

Abstract: Some deep-sea chemosynthetic invertebrates and their symbiotic bacteria can use molecular hydrogen (H 2 ) as their energy source. However, how much the chemosynthetic holobiont (endosymbiont-host association) physiologically depends on H 2 oxidation has not yet been determined. Here, we demonstrate that the Campylobacterota endosymbionts of the gastropod Alviniconcha marisindica in the Kairei and Edmond fields (kAlv and eAlv populations, respectively) of the Indian Ocean, utilize H 2 in response to their physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
(104 reference statements)
2
16
2
Order By: Relevance
“…We observed no change in expression for hydrogen oxidation genes in the A. boucheti symbiont under the experimental H 2 conditions. These findings differ from a recent study by Miyazaki et al [ 31 ], which showed that the campylobacterial symbiont of A. marisindica strictly regulates the expression of hydrogenases depending on the environmental hydrogen concentrations. Compared to Miyazaki et al [ 31 ], who provided 100 µM H 2 in their experiments, we only provided 25 µM H 2 .…”
Section: Discussioncontrasting
confidence: 99%
“…We observed no change in expression for hydrogen oxidation genes in the A. boucheti symbiont under the experimental H 2 conditions. These findings differ from a recent study by Miyazaki et al [ 31 ], which showed that the campylobacterial symbiont of A. marisindica strictly regulates the expression of hydrogenases depending on the environmental hydrogen concentrations. Compared to Miyazaki et al [ 31 ], who provided 100 µM H 2 in their experiments, we only provided 25 µM H 2 .…”
Section: Discussioncontrasting
confidence: 99%
“…The authors argue that these host distribution patterns likely reflect distinct metabolic capabilities or physiological needs of their symbionts. A recently confirmed capacity for H 2 oxidation in Alviniconcha campylobacterotal symbionts [25], first suggested by [23], appears to support this hypothesis. This would enable the use of discrete abundant energy resources in a highly limiting spatial environment.…”
Section: Discussionmentioning
confidence: 67%
“…Most Alviniconcha species, including A. kojimai and A. strummeri, host Gammaproteobacteria-dominated symbioses that are closely related to known chemoautotrophic [9-11, 14, 15], sulphur-oxidising bacteria that predominantly use the Calvin-Benson-Bassham cycle for carbon fixation [20]. In the remaining two species, A. boucheti and A. marisindica, symbioses are dominated by sulphur-oxidising bacteria from a separate phylum, the Campylobacterota [9,10] formerly known as the Epsilonproteobacteria [21,22] that also utilise H 2 -oxidation [23][24][25] under high-H 2 concentrations (several mM, [25]) and likely fix carbon through the Reverse Tricarboxylic Acid cycle [20]. Thus, one hypothesis that might explain the small-scale habitat partitioning observed in SW Pacific Alviniconcha species, is that optimal conditions for chemosynthesis differ for each host species, as a function of the unique metabolic capabilities or physiological requirements of their symbiont assemblages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During deep-sea sampling and onboard recovery, which usually takes more than an hour, the composition and activity of microbial communities can change considerably, while RNAs can be degraded (25), which means that true RNA profiles in the deep sea can be missed if experimental procedures are conducted after retrieval (26,27). To solve these problems, in situ RNA stabilization (i.e., stabilization before retrieval by remote control) instead of onboard RNA stabilization (i.e., stabilization after retrieval) is desirable (16,(28)(29)(30)(31)(32); however, these two approaches have been neither systematically compared nor applied to metatranscriptomic analyses of deep-sea symbiotic microbial communities.…”
mentioning
confidence: 99%